1989
DOI: 10.1021/bi00446a016
|View full text |Cite
|
Sign up to set email alerts
|

Purification of recombinant human tissue factor

Abstract: Tissue factor (TF) is a 263 amino acid membrane-bound procoagulant protein that serves as a cofactor for the serine protease factor VII (fVII). Recombinant human TF (rTF) produced in both human kidney 293 cells and Escherichia coli has been immunoaffinity purified by using a TF-specific monoclonal antibody. Recombinant TF produced in 293 cells is glycosylated and migrates on reducing SDS-PAGE with an apparent molecular weight (Mr) of 45K. Some interchain disulfide-bonded rTF dimers are observed under nonreduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 23 publications
(21 reference statements)
7
53
0
1
Order By: Relevance
“…The N-terminal analysis showed that both recombinant and placental proteins exist in two forms, a full-length form composed of 263 amino acid residues and a truncated form composed of 261 residues, where the first two amino acids on the N-terminus of the protein are missing. This observation was consistent with previously published data (Spicer et al , 1987 ;Paborsky et al , 1989 ). The fractional abundance of each form in the two proteins is different.…”
Section: Glycosylationsupporting
confidence: 83%
See 2 more Smart Citations
“…The N-terminal analysis showed that both recombinant and placental proteins exist in two forms, a full-length form composed of 263 amino acid residues and a truncated form composed of 261 residues, where the first two amino acids on the N-terminus of the protein are missing. This observation was consistent with previously published data (Spicer et al , 1987 ;Paborsky et al , 1989 ). The fractional abundance of each form in the two proteins is different.…”
Section: Glycosylationsupporting
confidence: 83%
“…The amino acid sequence data indicate that full-length TF has three potential glycosylation sites at Asn ) in the cytoplasmic domain (Paborsky et al , 1989 ;Paborsky and Harris , 1990 ). The latter site is not present in truncated TF proteins.…”
Section: Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue factor triggers the extrinsic coagulation pathway, plays a key role in homeostasis and in several thrombotic diseases, and is also involved in cell signaling (4)(5)(6)(7)(8)(9)(10). Tissue factor is a glycosylated membrane protein that consists of a single polypeptide chain of 263 amino acids with an apparent molecular mass of 46 kDa, as determined by SDS-PAGE electrophoresis (5,(11)(12)(13)(14). Glycosylation does not appear to be important for tissue factor function as the recombinant nonglycosylated protein retains procoagulant activity (12).…”
Section: The Structure and Location Of Tissue Factormentioning
confidence: 99%
“…Tissue factor is a glycosylated membrane protein that consists of a single polypeptide chain of 263 amino acids with an apparent molecular mass of 46 kDa, as determined by SDS-PAGE electrophoresis (5,(11)(12)(13)(14). Glycosylation does not appear to be important for tissue factor function as the recombinant nonglycosylated protein retains procoagulant activity (12). Tissue factor is a type I integral membrane protein.…”
Section: The Structure and Location Of Tissue Factormentioning
confidence: 99%